Pengembangan Wawasan Multikultural Antar Pemuka Agama - Aminuddin Mamma (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract The birth of various teaching or irrelevant understanding of a religion, such as materialism and secularism, the religion has been made helpless and put-aside from many aspects. This could also affect people if a religion is no longer effective within multi-dimension and multi-cultural life. This paper was meant to work through ways to be done in the middle of various growing culture in society where a more important role of religion leaders could help a much wider point of view in this dynamic globalization era among various yet sometimes dilemmatic solutions. In order to describe a religional life of a society, an observation and people's empowerment are both needed, such as religional infrastructures, understanding, actuating, religional institution, religion leaders, etc. Religion leaders are supposed to have a soothing dynamics inside multi-cultural society. Therefore they are supposed to have several principals, such as finding a point in common; pleasing and easing; and minding people's psychologicals. There are also several ethically signs, such as not separating the saying from the doing; avoiding religion tolerance; not insulting other religions' god; preventing social discrimination; not getting friends with sexually immoral perpetrators; and having intelligency.